Molecular recognition and solubility of mefenamic acid in water - Abdul Mudalip, Siti Kholijah; Abu Bakar, Mohd Rushdi; Jamal, Parveen; Adam, Fatmawati; Alam, Md Zahangir (Asian Publication Corporation, 2016)
Molecular dynamics (MD) simulations were performed using COMPASS force field and Ewald summation method that are available in the Material Studio simulation package. The aim of this work is to investigate the solubility and intermolecular interactions (i.e., hydrogen bonding) of water with mefenamic acid. The solubility of mefenamic acid in water is lower than the ideal solubility. The results of the simulation show that the density, diffusion coefficient and radial distribution functions (RDFs) calculated for water are comparable with the literature. Analysis of radial distribution functions in the binary system of mefenamic acid/water shows low hydrogen bond formation between mefenamic acid and water molecules as well as diffusivity. In addition, the strength of the interaction is much lower than that of hydrogen bonds formed between molecules of water. These findings suggest low diffusivity and poor solubility characteristic of mefenamic acid in water